Anlotinib dramatically improved pulmonary hypertension and hypoxia caused by Pulmonary Tumor Thrombotic Microangiopathy (PTTM) associated with gastric carcinoma: a case report - Wang, Yang; Ning, Wei-wei; Jin, Yi-fan; Zhu, Qing-qing; Wang, Zai-liang; Su, Nan; Chen, Yan-bin; Huang, Jian-an; Chen, Cheng (Thrombosis journal, 2023)
Background Pulmonary tumor thrombotic microangiopathy (PTTM) is a rare malignancy-related respiratory complication, demonstrating rapid progression of pulmonary hypertension (PH) and respiratory failure. Although a number of treatments have been attempted for patients diagnosed with or suspected of having PTTM, successful-treated cases of PTTM were mainly from imatinib therapy, which was a PDGF receptor inhibitor. Anlotinib was a novel tyrosine kinase inhibitor that targets VEGFR, FGFR, PDGFR, and c-kit. Case presentation We reported a patient of PTTM associated with gastric carcinoma, whom were treated with anlotinib, thereby exhibiting significant improvement of PH and respiratory dysfunction. Conclusion Our case provides a new understanding of therapy to PTTM, with implications for defining anlotinib as candidate drug for PTTM. Clinical diagnosis and prompt initiation of anlotinib might be one of the strategies in patients with unstable PTTM.